Biodegradation activities of microplastic polymers by Agelas conifera sponge-symbiotic bacteria - Meutia Samira Ismet; Endang Sunarwati Srimariana; Nur Alam Dwi Cahyati; Nurlita Putri Anggraini; Lenni Mariana Simbolon; Nadya Cakasana; Mohamad Rafi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Research on microplastic (MP) accumulation in marine organisms' tissue have been widely conducted, as well as research on microplastic biodegradation by microbial organisms from the environment.Agelas coniferasponge is proven to accumulate MP in its tissue as well as having bacteria as symbiotic organism. This research aims to screen and study biodegradation activities ofA. coniferasymbiotic bacteria on MP polymers, alsoto identify the species of those bacteria isolates. Bacterial Isolation ofA. coniferasponge tissue was using Zobell 2216E agar media. Screening and biodegradation assay of the bacteria isolates was conducted on Marine Salt Media agar that was added with 0,5 g of MP polymers, using Kroc-Boral method. Diameter of clear (bacterial growth) zone surrounding Kroc-Boral indicated the biodegradation activity of the bacterial isolates. Statistical analysis on the activity was using Two Way ANOVA. Results showed that there were 9 bacterial isolates of 53 that could degrade several MP polymers, with different activities (ANOVA, p value 0.05). High and low-density polymers (Linear- Low Density PolyEthylene/ LLDPE, Polyethylene/PE, and Polyvinyl Chloride/ PVC) were found to be degraded by all 9 isolates. Meanwhile, Polyethylen Taraphtalene (PET) and Polystyrene (PS) only degraded by 8 and 3 isolates, respectively. There are only 5 isolates that have high biodegradation index (1.5) on different polymers, which mostly on PET polymer. Isolate Ac8MP found to be the most bacteria that have degradation index on all polymers more than 1.This research proves that symbiotic bacteria could have a biodegradation mechanism on MP polymers that accumulates by sponge-host. However, further study needs to be done to understand the mechanisms and effectiveness of sponge-bacterial biodegradation activity.